2019
DOI: 10.1007/978-3-030-36030-6_11
|View full text |Cite
|
Sign up to set email alerts
|

General Linear Group Action on Tensors: A Candidate for Post-quantum Cryptography

Abstract: Starting from the one-way group action framework of Brassard and Yung (Crypto '90), we revisit building cryptography based on group actions. Several previous candidates for oneway group actions no longer stand, due to progress both on classical algorithms (e.g., graph isomorphism) and quantum algorithms (e.g., discrete logarithm).We propose the general linear group action on tensors as a new candidate to build cryptography based on group actions. Recent works (Futorny-Grochow-Sergeichuk Lin. Alg. Appl., 2019) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 90 publications
0
18
0
1
Order By: Relevance
“…Cryptographic group actions have received substantially less attention compared to traditional group-theoretic assumptions. Nonetheless, there have been a small number of works studying various candidate cryptographic group actions [GS10,JQSY19] and their hardness properties [BY91,GPSV18]. In terms of public-key primitives, these works have demonstrated that cryptographic group actions endowed with some hardness properties imply PKE and noninteractive key exchange (NIKE).…”
Section: Cryptographic Group Actionsmentioning
confidence: 99%
“…Cryptographic group actions have received substantially less attention compared to traditional group-theoretic assumptions. Nonetheless, there have been a small number of works studying various candidate cryptographic group actions [GS10,JQSY19] and their hardness properties [BY91,GPSV18]. In terms of public-key primitives, these works have demonstrated that cryptographic group actions endowed with some hardness properties imply PKE and noninteractive key exchange (NIKE).…”
Section: Cryptographic Group Actionsmentioning
confidence: 99%
“…Grup General Linear pada tensor yang merupakan bentuk lebih umum dari , ℂ juga masih menjadi objek yang masih terus diteliti, hal ini ditunjukan dengan adanya paper [4] yang juga membahas aplikasi tindakan grup general linear pada kriptografi. Tindakan grup yang diperoleh digunakan untuk membangun suatu skema untuk enkripsi public-key.…”
Section: Pendahuluanunclassified
“…Cryptographic group actions are recently gaining a renewed attention from the perspective of postquantum cryptography. Ji et al [JQSY19] proposed new instantiations based on general linear group We remark that the meaning of "swap" here is different from that of the SWAP gate as explained below. The distinguishing advantage is (necessarily) halved.…”
mentioning
confidence: 99%
“…An important difference between the instantiations in [JQSY19] and [ADMP20] is that the former considers non-abelian groups whereas the latter considers abelian groups. Abelian group actions are particularly useful because they give rise to a non-interactive key exchange protocol similar to Diffie-Hellman key exchange [DH76].…”
mentioning
confidence: 99%
See 1 more Smart Citation